Comparison of hepatitis B vaccine efficacy in Japanese students: a retrospective study - Masanori Ogawa; Dai Akine; Teppei Sasahara (Komiyama Printing Co. Ltd, 2019)
Abstract Background Two types of recombinant hepatitis B virus (HBV) vaccines are available in Japan. One type uses the antigen from genotype A (Heptavax-II®) and the other uses the antigen from genotype C (Bimmugen®). Potential differences in productivity of the hepatitis B virus surface (HBs) antibody between vaccines have not been studied in detail. We investigated the acquired level of immunity against HBV in association with two vaccines, their administration routes, and patient sex. We present the appropriate inoculation method based on the characteristics of each vaccine. Methods Data of 1135 medical and nursing students (481 men and 651 women) were used, each of whom was unvaccinated prior to recruitment and subsequently vaccinated three times prior to the study. The vaccine type and administration route differed according to the university department and enrolling year. The students were categorized into the following three groups: Bimmugen®-subcutaneous group, Heptavax-II®-subcutaneous group, and Heptavax-II®-intramuscular group. The total and sex-segregated positive rates of the HBs antibody among the three groups were compared using Pearson's chi-square test. The effect of time between the HBs antibody test and vaccine administration on the HBs antibody level was also analyzed similarly. Results The Bimmugen®-subcutaneous group showed the highest positive HBs antibody rate (92.0%) among the three groups. In the Heptavax-II® group, the positive rate was 66.3% in the subcutaneous injection group and 89.1% in the intramuscular injection group. There was a significant difference among these three groups. In terms of sex, women showed a significantly higher average positive rate than men in each group. In terms of effect of time between the HBs antibody test and vaccine administration, no significant differences were observed. Conclusions Bimmugen® is associated with more effective HBs antibody production than Heptavax-II® in Japanese students. However, the Heptavax-II® vaccine is an appropriate choice for HBV vaccination in areas where HB is caused predominantly by HBV genotype C. With both vaccines, women tended to acquire more immunogenicity than men. Intramuscular injection may be the preferred administration route due to the possibility of local reactions.